BIOMASSA HIJAUAN Mucuna bracteata DAN PENGARUHNYA TERHADAP KADAR N TANAH DI PERKEBUNAN KELAPA SAWIT - Ir. Mardiana Wahyuni, MP (Institut Teknologi Sawit Indonesia, 2019)
Mucuna bracteata is one of the legume cover crop that is usually used in oil palm and rubber plantations. In general, legume cover crop are planted during the preparation / after land clearing when the oil palm are planted, Mucuna bracteata has covered the planting area. Mucuna bracteata growth conditions will affect soil biological properties, namely organic nutrient content, C/N balance, microbial population and macro-fauna activity. This study aimed to describe the soil and Mucuna bracteata plants in the phase of oil palm plants. The study was conducted in April - June 2019 in the area of ​​TBM 3 oil palm plantations in 2 locations, namely Pabatu Plantation and Tinjowan Plantation. Soil types in Pabatu Plantation are typic dystrudepts (Reddish Brown Podsolik) and in Tinjowan Plantation the type of soil is typic hapludults (Yellowish Red Podsolik) and some typic paleudults (Yellow Podsolik). This study used a descriptive design that describes the growth character / biomass of Mucuna bracteata on TBM 3 oil palm plantations. The results of this study are the fresh biomass of Mucuna bracteata in Pabatu Plantation is 43,260 kg / ha and Tinjowan Plantation is 34,146 kg / ha (79%) and dry biomass is 13,943 kg / ha in Pabatu Plantation and 12,705 kg / ha in Tinjowan Plantation. The levels of N leaves of Mucuna bracteata are in the high category. Soil organic matter content and total N in Pabatu and Tinjowan Plantation are in the low category.